IMPROVING THE STUDENTS’ MOTIVATION IN SPEAKING BY USING PICTORIAL RIDDLE - Muhalim, Muhalim (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
This research purposed to find out how the Pictorial Riddle Approach improves the students’ motivation in speaking accuracy and speaking fluency   at the Second Year students of SMA Muhammadiyah 4 Makassar. This research was a classroom action research (CAR) which consisted of two cycles in which every cycle consisted of four meetings. The subject of this research was one of classes with the total of students is 26 students. The instruments were questionnaire, speaking test and observation sheet. The research findings indicated that using Pictorial Riddle Approach could improve the students’ motivation in speaking term of speaking accuracy and speaking fluency, from table 6 indicated that there was improvement the students’ speaking accuracy from D-test to Cycle I was 16.45 %, the increase of the students’ speaking accuracy from Cycle I to cycle II was 9.72 % and the increase of the students’ speaking accuracy from D-test to cycle II was 25.65%. The other hand the students’ speaking fluency from diagnostic test to cycle I was 1.54 %, the increase of the students’ speaking fluency from cycle I to cycle II was 0.73 %. The students’ frequency and percentage of D-Test in Questionnaire for D-Test for positive statement/favorable is 31.51 % students disagree, in negative statement/unfavorable is 27.30 students get undecided, means score was 51.57 as low motivation. In Cycle I for positive statement is 34.22 % students get undecided, in negative statement/unfavorable is 37.68 % students get undecided, mean score was 67.57 as average motivation. After taking Cycle II positive statement/favorable is 43.07 % students get agree and the negative statement/unfavorable is 46.15 % students get agree, mean score was 79.42 as high motivation. Based on the result of the data analysis above, the researcher concluded that the students’ at The Second Year Students of SMA Muhammadiyah 4 Makassar had high motivation, active in speaking focus on accuracy and fluency in English. It means that Pictorial Riddle Approach can improve the students’ motivation in speaking.